RELATIONSHIP OF P WAVE DISPERSION AND LEFT VENTRICULAR HYPERTROPHY AMONG HYPERTENSIVES. (April 2021) - Inofomoh, Francisca; Familoni, Oluranti; Amadi, Casmir; Kushimo, Oyewole
Abstract : Objective: Cardiovascular diseases constitute a global problem. Hypertension is the single most important cardiovascular risk factor for coronary heart disease, congestive heart failure and stroke. Late detection, poor risk stratification and suboptimal management leads to increased mortality. Electrocardiography (ECG) is cheap, easily accessible and useful tool to identify early markers of arrhythmias such as P wave dispersion (PWD) and hypertensive target organ damage like LVH. This study aimed to assess the relationship of PWD and LVH among hypertensive subjects, comparing with normotensive controls and to analyse whether PWD correlates with other cardiovascular risk factors. Design and method: 150 hypertensives; 25–75 years from cardiology outpatient clinic enrolled with 150 age and sex matched controls. Informed consent taken, clinical history, anthropometric measurements, standard 12 lead ECG and echocardiography were done for all 300 participants following standard operating procedures. P-wave duration assessed using digital measurements of all leads; PWD calculated as difference between maximum and minimum P wave durations, LVH was determined using the sokolow-lyon criteria on ECG and Left Ventricular Mass Indexed to height2.7 on echocardiography. Left ventricular systolic and diastolic functions were assessed. Results: Of 300 participants; 49.3% were males. Mean age of total population was 42.26 ± 11.55 years. Mean Body Mass Index of subjects (26.84 ± 3.64 kg/m2) significantly higher than controls (25.32 ± 3.22)P = <0.001. Likewise the mean waist circumference of the subjects (95.74 ± 11.08 cm) vs. (92.24 ± 9.62 cm), p = 0.004. Mean P wave dispersion among subjects was 38.29 ± 8.02ms compared to controls; 32.11 ± 4.72ms, P < 0.001. Mean Left Ventricular Mass Index(LVMI)to height was also significantly higher among subjects compared to control; 42.04 ± 15.55 g/ht2.7 vs. 34.24 ± 10.01 g/ht2.7, P < 0.001. In this study, prevalence of prolonged P wave dispersion among subjects(105)70.0% was significantly higher than(49) 32.6% in the controls, P < 0.001. The correlation of P wave dispersion and left ventricular systolic function (EF) showed inverse relationship r = -0.17 and P = 0.03. A linear positive relations was observed between P wave dispersion and waist circumference r = 0.23, P = 0.004. Conclusions: PWD & LVMI are increased in hypertensives; prolonged P wave dispersion is an indicator of presence of other cardiovascular risk factors.